Africa's digital future From theory to action - Jansen van Rensburg, Susara J. (The future of international trade and development, 2021)
The main thrust of this book is to examine whether Africa is in a position to benefit from the digital age, given the continent's many development challenges and slow adoption of digital technologies. While there is substantial literature on the digital economy and the quickening pace of the Fourth Industrial Revolution (4IR), comparatively little research has been conducted on what the digital age means for Africa. This book aims to close this research gap by using various qualitative and quantitative research methodologies to arrive at a cross-section of original findings and perspectives on how Africa can capitalise on the benefits of digital developments, including their potential to create jobs and bring about more inclusive growth. The book's main contribution is its coverage of a range of topics that will affect Africa's digital future, including industrialisation, global value chains, transport and logistics, trade facilitation, labour-market dynamics, employment and education. The theme of digital trade forms a backdrop to many of the chapters, along with references to the COVID-19 pandemic. The book acknowledges that although African countries should learn from international best practices, they need to chart their own course according to their own particular circumstances. By adopting a digital mindset, countries should be able to diversify economically and extend their market reach across the continent. Furthermore, while Africa should be looking to the future and determining how digital technologies can become effective tools of sustainable development, the continent has much catching up to do.